Correlation Between Axial Length and Amplitude of Accommodation in Myopia Patients - Evelyn Angie; Aryani Atiyatul Amra; Masitha Dewi Sari (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Background: Myopia is the most common refractive disorder and is a global concern because it can cause more serious eye problems. Excessive prolonged axial growth of the eyeball can lead to myopia. The amplitude of accommodation is the strength of the eye accommodation during the minimum and maximum accommodation conditions. Based on the above data, the researchers wanted to assess the relationship between eyeball length and accommodation amplitude in myopia patients. Method: The research was conducted at the Hospital of Prof CPL University of North Sumatra from November 2023 to March 2024. Data analysis was done analytically and presented in the form of data tabulation. Result: This study included 54 myopia patients, 27 males and 27 females, who visited the eye clinic. The mean age of the subjects was (52%). The mean age of the subjects was 23 years old with the youngest being 22 years old and the oldest being 24 years old. The mean of axial length for mild myopia, moderate myopia and severe myopia were 24.51 cm, 25.75 cm and 28.38 cm respectively. The lowest NPA value was found in severe myopia (27.33 cm) and the highest in mild myopia (43 cm). The lowest NPC value was found in mild myopia (36.61 cm) and the highest in severe myopia (38.56 cm). There was a significant relationship between eyeball length and accommodation amplitude with a Spearman correlation value of -0.685 as well as after cycloplegic administration with a Spearman correlation value of 0.438. NPA values showed an increase when receiving spherical correction, whether accompanied by cycloplegics or not, and a decrease when not receiving spherical correction. NPC values showed a decrease in all treatments. Conclusion: There is a correlation between axial length and amplitude of accomodation values (NPA and NPC) in patients with myopia.